Perencanaan Strategis Program CSR Pada Suppliyer Rajungan di Lamongan: Mengidentifikasi Prioritas dan Tujuan Yang Berkelanjutan: Studi Kasus: UD. Aulia - Shofinatul Wahdah Nur Aulia; Masiyah Kholmi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Corporate Social Responsibility (CSR) is a must for companies that want to build a sustainable reputation and support the development of the surrounding community. This research discusses the strategic planning of the Corporate Social Responsibility (CSR) program for crab suppliers in Lamongan, with a case study at UD. Aulia. The aim of this research is to identify sustainable priorities and goals to ensure CSR programs provide long-term benefits for local communities and the environment. Through a qualitative approach, this research explores the important role of Human Resources (HR) in supporting and implementing CSR in companies. The research results show that effective HR practices, such as employee training and development and diversity policies, have a significant contribution to the success of CSR programs. The social impact of CSR programs includes increasing community economic welfare, reducing unemployment, and preserving marine ecosystems. The economic impact includes the creation of new jobs and increased fishermen's income. Thus, strategic planning for the CSR program at UD. Aulia is able to create a sustainable positive impact on society and the environment through identifying the right priorities and inclusive collaboration with crab suppliers.